2007
DOI: 10.1111/j.1600-0854.2007.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Trafficking of the Secretory Proprotein Convertase PCSK9 and Its Dependence on the LDLR

Abstract: Mutations in the proprotein convertase PCSK9 gene are associated with autosomal dominant familial hyper-or hypocholesterolemia. These phenotypes are caused by a gain or loss of function of proprotein convertase subtilisin kexin 9 (PCSK9) to elicit the degradation of the lowdensity lipoprotein receptor (LDLR) protein. Herein, we asked whether the subcellular localization of wild-type PCSK9 or mutants of PCSK9 and the LDLR would provide insight into the mechanism of PCSK9-dependent LDLR degradation. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
172
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(186 citation statements)
references
References 48 publications
14
172
0
Order By: Relevance
“…An alternative hypothesis, and one consistent with current knowledge, would be the absence of proteolytic activity altogether, whereby binding of PCSK9 to LDLR (or other receptor) provides a signal to lower LDLR levels. A recent publication by Nassoury et al (32) has provided evidence that the CRD binds to the cell surface via LDLR. A nonproteolytic mechanism has been shown to exist in proteases of the trypsin family such as hepatocyte growth factor (HGF) (33), whereby the protease has lost catalytic activity but functions as a growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis, and one consistent with current knowledge, would be the absence of proteolytic activity altogether, whereby binding of PCSK9 to LDLR (or other receptor) provides a signal to lower LDLR levels. A recent publication by Nassoury et al (32) has provided evidence that the CRD binds to the cell surface via LDLR. A nonproteolytic mechanism has been shown to exist in proteases of the trypsin family such as hepatocyte growth factor (HGF) (33), whereby the protease has lost catalytic activity but functions as a growth factor receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The current studies provide direct experimental evidence that exogenously added PCSK9 reduces LDLRs in a manner that requires LDLR binding but not catalytic activity. Studies by Maxwell et al (25) showed that overexpression of PCSK9 in HepG2 cells induces degradation of LDLRs intracellularly in a post-ER compartment, and Nassoury et al (26) have suggested that the two proteins interact in the ER and co-localize in the Golgi apparatus in hepatocytes. The results of our studies do not preclude the possibility that PCSK9 can function intracellularly in a manner that requires catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the proprotein convertases subtilisin kexin 9 (PCSK9) gene (4), which is highly expressed in liver and small intestine (5), was identified as the third locus associated with familial hypercholesterolemia (6). It is now clear that PCSK9 binds the LDLR and triggers its intracellular degradation in acidic compartments, resulting in increased circulating plasma cholesterol (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Overexpression studies in liver suggested that both intraand extracellular PCSK9 target the LDLR (9,15,16) toward degradation in late endosomes/lysosomes (LE/L) (7)(8)(9)(10). It was shown that the adaptor protein ARH, which interacts with the cytosolic tail of the LDLR, is essential for the endocytosis and degradation of the cell surface PCSK9⅐LDLR complex in vivo (16).…”
mentioning
confidence: 99%